Muhammadiyah Sebagai Gerakan Islam Berwatak Tajdid dan Tajrid - Panca hardian Putra; Ricko Sholeh Pratama; Rahayu Lestari; Marzelina Sintia Putri; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The role of Muhammadiyah as a modernist Islamic movement in Indonesia with a focus on two main characters, namely tajdid (renewal) and tarjih (legal selection). Tajdid is the basis of the movement to respond to the challenges of the times without leaving the authentic teachings of Islam, while tarjih functions as a methodological guideline in making legal decisions based on the Qur'an and Sunnah. By combining tajdid and tarjih, Muhammadiyah seeks to actualize Islam in a dynamic socio-community context and make a significant contribution to national development. The purpose of this study is to reveal Muhammadiyah as an Islamic Movement with Tajrid and Tajdid Characters. The research method used in this study is a qualitative method, by using books, magazines, articles and other sources both offline an online as the main data sources in addition to interviewing Muhammadiyah figures around. The results of this study indicate that Muhammadiyah often describes this organization as an Islamic movement that has tajrid (purification) and tajdid (renewal) characters. Muhammadiyah was founded by KH. Ahmad Dahlan in 1912 with the aim of returning Islamic teachings to their original sources, namely the Qur'an and Sunnah